2017
DOI: 10.1109/lra.2017.2660060
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Flow Awareness for Mobile Robots in Partially Observable Environments

Abstract: This is the accepted version of a paper published in IEEE Robotics and Automation Letters. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…In the future, it is possible to replace the von Mises distribution with a Gaussian distribution or replace the Bernoulli likelihood in [20] with a Gaussian likelihood to accurately model such spatial density estimations. 4) CLiFF-Map Model: Circular Linear Flow Field map (CLiFF-map) [33] is a technique for encoding patterns of movement as a field of Gaussian mixtures. They can be combined with semi-wrapped Guassian mixture models (SWGMM) to model multi-modal motion.…”
Section: B Evaluation Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, it is possible to replace the von Mises distribution with a Gaussian distribution or replace the Bernoulli likelihood in [20] with a Gaussian likelihood to accurately model such spatial density estimations. 4) CLiFF-Map Model: Circular Linear Flow Field map (CLiFF-map) [33] is a technique for encoding patterns of movement as a field of Gaussian mixtures. They can be combined with semi-wrapped Guassian mixture models (SWGMM) to model multi-modal motion.…”
Section: B Evaluation Methodsologymentioning
confidence: 99%
“…Kucner et al also improved their approach in [11] and proposed a continuous representation in [32]. To model speed and direction of people, [33] introduced an expectation-maximisation scheme based on the Independent von MisesGaussian distributions [34]. They also showed that the model of the movement of people could be used to achieve more efficient navigation of the robot through human crowds [35].…”
Section: Related Workmentioning
confidence: 99%
“…Unlike the work of Ramos et al [25], which is aimed primarily at modelling the spatial structure, and [22], which aims to make short-term predictions of the motion of people, our aim is to create universal, spatial-temporal models capable of long-term predictions of various phenomena. Inspired by the ability of the continuous models [25], [22] to represent spatio-temporal phenomena and the predictive power of spectral representations [5], we propose a novel method which allows to introduce the notion of time into state-of-the-art spatial models used in mobile robotics. Unlike our previous work [5], which treats environmental states as independent despite their spatial proximity and is applicable to binary states only, the proposed method can be applied to continuous, multi-dimensional representations, e.g.…”
Section: Related Workmentioning
confidence: 99%
“…The Circular Linear Flow Field map (CLiFF-map) [10] describes motion patterns as a field of Gaussian mixtures whose local elements are probability distribution of (instantaneous) velocities V V V = (θ, ρ), where θ ∈ [0, 2π) is the orientation and ρ ∈ R + the speed. This is a heterogeneous vector with one circular random variable (θ) and one linear (ρ).…”
Section: Cliff-map Modelmentioning
confidence: 99%
“…Unlike [11,14,12,9] we use a more powerful probabilistic representation than vector fields named Circular Linear Flow Field (CLiFF) map [10]. It associates a Gaussian mixture model to each location whose components encode multiple weighted flow directions.…”
Section: Introductionmentioning
confidence: 99%